Caracterización cromosómica de Rhodolirium laetum (Phil.) Ravenna (Amaryllidaceae) a través de cariotipificación e hibridación in-situ de ADN ribosómico - Baeza, Carlos M.; García, Nicolás; Herrera, Fernanda; Ruiz, Eduardo; Rosas, Marcelo (Gayana Botánica, 2017)
Rhodolirium laetum (Phil.) Ravenna has a karyotype 2n = 2x = 16 and the haploid formula 4m + 2sm + 2st. One pair of rDNA 45S signals and two pairs of rDNA 5S were detected through fluorescent in-situ hybridization. The results are discussed in the context of Traubiinae.